Controlling Spare Parts Inventory of PT Hasura Mitra Gemilang's Production Machines Using the EOQ Method - Sandya, Astriyani; Asyifa, Karina; Arham, Raissa; Merdiyanti, Angelia (Neo Journal of economy and social humanities, 2025)
Controlling production machine spare parts inventory is crucial for a manufacturing company like PT Hasura Mitra Gemilang to ensure that production activities continue smoothly. The most frequently used spare part is the Nozzle Heater 40x40mm 220-volt. The objectives of this research are: (1) To determine the economic order quantity, (2) To determine the safety stock level that should be maintained, and (3) To determine the reorder point. The analysis uses the Economic Order Quantity (EOQ) method. The analysis results show that in 2024, the need for Nozzle Heater 40x40 mm 220-volt s is 353 units, the optimal order quantity is 62 units, the order frequency is 6 times, the safety stock is 7 units, the reorder point in inventory is 14 units, and the company can save inventory costs amounting to Rp. 102,330. In 2025, the demand for Nozzle Heater 40x40 mm 220-volt s is 410 units, the optimal order quantity is 67 units, the order frequency is 6 times, the safety stock is 7 units, the reorder point in inventory is 14 units, and the company can save inventory costs of Rp. 125,520.